Manufacturing method of PC stone-like water permeable brick capable of melting snow
By using PC imitation stone permeable bricks that can melt snow on urban pavements, the problem of existing pavement materials being unable to penetrate rainfall and the pavement loses anti-slip after snow melting in winter is solved, and the road surface safety and service life are improved.
Patent Information
- Application Number
- CN202411911317.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing urban pavement materials cannot effectively penetrate the rainfall, resulting in rainwater being unable to enter the soil, and the pavement loses its anti-slip performance after the snowfall melts in winter, which poses a safety hazard.
A method of manufacturing a PC imitation stone permeable brick that can melt snow is adopted. By combining gelling materials and auxiliary materials, a surface layer with a certain hardening layer is formed, and reducing iron powder and anticoagulant are added to the bottom layer to release heat through the oxidation reaction and reduce the difficulty of ice formation.
The active snow melting function of permeable bricks is realized, the anti-slip performance is maintained, the road safety is improved, and the service life of permeable bricks is extended.
Smart Images

Figure CN119683939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sponge cities, and in particular to a method for manufacturing PC imitation stone permeable bricks capable of melting snow. Background Art
[0002] Sponge city is a new generation of urban stormwater management concept, which means that the city can be like a sponge, with good "elasticity" in adapting to environmental changes and responding to natural disasters caused by rainwater. It can also be called a "water-elastic city". It has the functions of absorbing water, storing water, infiltrating water, purifying water and releasing water. When a sponge city wants to infiltrate water, it needs to infiltrate natural rainfall into the hardened urban surface. However, most of the current urban roads are reinforced concrete roads or cement bricks, and natural precipitation cannot penetrate into the soil of the road surface.
[0003] In the prior art, some cities also use a large number of permeable bricks, because the snow in northern cities in winter will fall on the permeable bricks, and then after being crushed by people or vehicles, it will cause the snow to melt and freeze, making the road surface abnormally slippery, posing a great safety hazard. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a method for manufacturing PC imitation stone permeable bricks that can melt snow. The permeable bricks manufactured according to the method can actively melt snow, so that the anti-slip surface of the original permeable brick top surface is no longer ineffective, thereby improving the safety of the permeable bricks.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] A method for manufacturing a PC imitation stone permeable brick capable of melting snow comprises the following steps:
[0007] S1. Proportion of the surface materials of the permeable bricks: The surface layer is divided into cementitious materials and auxiliary materials, wherein the cementitious materials include water-based resin and silicate cement; the auxiliary materials include quartz sand, tailings sand, anti-icing agent and surfactant, and the cementitious materials and auxiliary materials are stirred and mixed according to the proportion;
[0008] S2. Ratio of bottom materials of permeable bricks: The bottom layer includes mixed cement, condensation nucleus material, reduced iron powder, anti-icing agent and high-efficiency water reducing agent. The condensation nucleus material is used as the core to mix the mixed cement, anti-icing agent and high-efficiency water reducing agent into a spherical shape;
[0009] S3, shock-pressing molding: the surface layer material and the bottom layer material are successively put into the shock-pressing brick-making machine to form the primary product of permeable bricks through shock-pressing.
[0010] S4. Enhanced product functions: After the permeable bricks are cured in the curing room, hardener and anti-icing coating are sprayed on their surface.
[0011] Preferably, the water-based resin in the cementitious material accounts for 3%-8%, and the silicate cement accounts for 3%-8%; the auxiliary materials include quartz sand accounting for 5%-15%, tailings sand accounting for 60%-80%, anti-icing agent accounting for 3%-10%, and surfactant accounting for 1%-5%, and the above percentages are all mass percentages.
[0012] Preferably, the mixed cement in the base material accounts for 15%-25%, 0mm-3mm iron tailings and 3mm-5mm basalt account for 60%-75%, reduced iron powder accounts for 3%-8%, anti-icing agent accounts for 3%-10%, and high-efficiency water reducer accounts for 1%-5%, and the above percentages are all mass percentages; wherein the mixed cement is a mixture of silicate cement and aluminum sulfate cement in a 1:1 ratio.
[0013] Preferably, the anti-icing agent is one or more combinations of Mafilon, sodium chloride, calcium chloride or potassium acetate.
[0014] Preferably, the surfactant is one or more of anionic, nonionic or amphoteric surfactants, which are used to improve the dispersibility and fluidity of the material.
[0015] Preferably, the reduced iron powder is iron powder that has been subjected to reduction treatment, and its particle size is controlled below 100 meshes to ensure sufficient reaction with the infiltrated water to release heat.
[0016] Preferably, the high-efficiency water reducing agent is one or more of polycarboxylic acid-based, naphthalene-based or lignin-based high-efficiency water reducing agents, which are used to reduce water consumption and improve the density and strength of the permeable bricks.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects:
[0018] The present invention can utilize cementitious materials and auxiliary materials to mix with each other to form a surface layer with a certain hardened layer, which can not only facilitate the load-bearing of permeable bricks, but also reduce the occurrence of aggravated wear caused by repeated friction between permeable bricks and external objects. The present invention adds reduced iron powder to the bottom layer of permeable bricks. Through the melting of snow water and contact with reduced iron powder, the reduced iron powder can utilize the oxygen in the snow water to undergo oxidation reaction, release heat, increase the difficulty of snow water condensing into ice, and also improve the safety of permeable brick pavement. At the same time, anti-icing materials are also mixed into the bottom material of the permeable bricks, and are mixed with mixed cement, condensation nucleus material, reduced iron powder, anti-icing agent and high-efficiency water reducing agent to form a sphere, which can be slowly released into the snow water, reducing the freezing point of the snow water, and further increasing the difficulty of snow water condensing into ice. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0020] Figure 1 It is a schematic diagram of the main structure of the present invention;
[0021] Figure 2 It is a schematic diagram of the three-dimensional structure of the drum from the side;
[0022] Among them, 1. base; 2. legs; 3. roller; 4. baffle; 5. first cover plate; 6. first feed barrel; 7. second cover plate; 8. second feed barrel; 9. limit plate; 10. first air inlet pipe; 11. second air inlet pipe; 12. auger; 13. mixer; 14. gear ring; 15. gear; 16. motor. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] It should be noted that all components in the technical solution of this application require the necessary additional facilities of water supply, oil supply, electricity supply and gas supply to be driven and / or controlled. If there is no further explanation, it is assumed that the existing technology is used and equipped without special explanation.
[0025] It should be noted that, in order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0026] Embodiment 1:
[0027] Depend on Figure 1-2 The manufacturing method of a PC imitation stone permeable brick capable of melting snow comprises the following steps:
[0028] S1. Proportion of the surface materials of the permeable bricks: The surface layer is divided into cementitious materials and auxiliary materials, wherein the cementitious materials include water-based resin and silicate cement, and the water-based resin is water-based epoxy resin. The auxiliary materials include quartz sand, tailings sand, anti-icing agent and surfactant. The cementitious materials and auxiliary materials are mixed according to the proportion;
[0029] S2. Ratio of bottom materials of permeable bricks: The bottom layer includes mixed cement, condensation nucleus material, reduced iron powder, anti-icing agent and high-efficiency water reducing agent. The condensation nucleus material is used as the core to mix the mixed cement, anti-icing agent and high-efficiency water reducing agent into a spherical shape;
[0030] S3, shock-pressing molding: the surface layer material and the bottom layer material are successively put into the shock-pressing brick-making machine to form the primary product of permeable bricks through shock-pressing.
[0031] S4. Enhanced product functions: After the permeable bricks are cured in the curing room, hardener and anti-icing coating are sprayed on their surface.
[0032] According to the further optimization plan, the water-based resin in the cementitious material accounts for 3%-8%, and the silicate cement accounts for 3%-8%; the quartz sand in the auxiliary materials accounts for 5%-15%, the tailings sand accounts for 60%-80%, the anti-icing agent accounts for 3%-10%, and the surfactant accounts for 1%-5%. The above percentages are all mass percentages.
[0033] According to the further optimization plan, the mixed cement in the base material accounts for 15%-25%, 0mm-3mm iron tailings and 3mm-5mm basalt account for 60%-75%, reduced iron powder accounts for 3%-8%, anti-icing agent accounts for 3%-10%, and high-efficiency water reducer accounts for 1%-5%. The above percentages are all mass percentages; the mixed cement is a mixture of silicate cement and aluminum sulfate cement in a 1:1 ratio.
[0034] Furthermore, during the production process of the base material, tailings slag and basalt are needed as the core, and mixed cement, reduced iron powder, anti-icing agent and water reducer are wrapped on the outside. The spheroidizing equipment is used to form spheres, and the cement can be used to adhere to each other. At the same time, the gaps between the mutually adhered spherical base materials have certain permeable gaps, so that rain and snow water can flow out from the gaps into the soil under the permeable bricks.
[0035] The main components of silicate cement in mixed cement are tricalcium silicate and dicalcium silicate, while aluminum sulfate cement is mainly composed of anhydrous calcium sulfoaluminate and dicalcium silicate. The hydration products of aluminum sulfate cement mainly include calcium sulfoaluminite, aluminum gel and iron gel, etc. Its initial setting time is usually within 30-50 minutes, and the final setting time is within 40-90 minutes, which is much faster than that of silicate cement. Aluminum sulfate cement can quickly lock the reduced iron powder to prevent the reduced iron powder from contacting with oxygen in water too early, and then oxidizing and failing.
[0036] In terms of physical properties, sulphoaluminate cement has the characteristics of high early strength, high impermeability, high frost resistance, and micro expansion. The pore structure formed by its solidification is significantly different from that of silicate cement, with low total porosity and small pore size. This structure makes it have excellent impermeability, frost resistance, corrosion resistance, and shrinkage. It can be mixed with silicate cement to form pores that slowly release anti-icing agents and reduced iron powder, thereby increasing the service life of permeable bricks.
[0037] Furthermore, the spheroidizing device for the bottom material includes a base 1, two legs 2 are fixedly connected to the top surface of the base 1, a roller 3 is rotatably connected to the top surface of the two legs 2, a baffle 4 is fixedly connected to the side wall of the inner cavity of the roller 3, a first cover plate 5 is detachably connected to one end of the roller 3, a first feed barrel 6 is rotatably connected to the center of the first cover plate 5 through a bearing, a second cover plate 7 is fixedly connected to the other end of the roller 3, one end of the baffle 4 is detachably connected to the first cover plate 5, and the other end of the baffle 4 is fixedly connected to the second cover plate 7. A second feed barrel 8 is rotatably connected to the center of the second cover plate 7 through a bearing, and the inner wall of the end of the first feed barrel 6 and the second feed barrel 8 away from the roller 3 is limitedly rotatably connected to a limit plate 9, and the limit plate 9 can only be turned from the outside toward the roller 3. The top of the limit plate 9 is rotatably connected to the inner wall of the end of the first feed barrel 6 and the second feed barrel 8 away from the drum 3 through a torsion spring; the first air inlet pipe 10 and the second air inlet pipe 11 are fixedly connected and connected between the limit plates 9 of the first feed barrel 6 and the second feed barrel 8 and the drum 3. The first air inlet pipe 10 and the second air inlet pipe 11 are fixedly connected and connected to the external high-pressure air source respectively; the end of the second feed barrel 8 away from the drum 3 is fixedly connected and connected to an auger 12, and the feeding end of the auger 12 is connected to a mixer 13, which is a planetary mixer 13, which can fully mix the mixed cement, reduced iron powder, anti-icing agent and water reducer. A gear ring 14 is sleeved and fixedly connected to the outside of one end of the drum 3, and the gear ring 14 is meshingly connected to a gear 15, and the gear 15 is connected to a motor 16, and the motor 16 is fixedly connected to one of the legs 2. In order to facilitate the overall control of the spheroidizing equipment, a PLC controller is also provided, and the PLC controller is electrically connected to the motor 16, the auger 12, the mixer 13 and the high-pressure gas source, respectively, thereby improving the automation of the spheroidizing equipment. The PLC controller is a prior art and will not be described in detail herein, nor will it be shown in the accompanying drawings. In a further optimized solution, the anti-icing agent is one or more combinations of Mafilon, sodium chloride, calcium chloride or potassium acetate. Mafilon is preferably used as the anti-icing agent, which has a porous structure of volcanic rock powder that absorbs salts. It can gradually seep out from the permeable bricks under the rolling of cars, etc., and play an anti-icing role.
[0038] In a further optimized solution, the surfactant is one or more of anionic, nonionic or amphoteric surfactants, which are used to improve the dispersibility and fluidity of the material.
[0039] According to a further optimization scheme, the reduced iron powder is iron powder that has been subjected to reduction treatment, and its particle size is controlled below 100 meshes to ensure sufficient reaction with the infiltrated water to release heat.
[0040] In a further optimized solution, the high-efficiency water reducer is one or more of polycarboxylic acid-based, naphthalene-based or lignin-based high-efficiency water reducers, which are used to reduce water consumption and improve the density and strength of permeable bricks. Permeable bricks preferably use polycarboxylic acid water reducers, which contain a variety of alcohols and acidic components, which can not only improve the strength of concrete, but also help release anti-icing agents.
[0041] The working process of this embodiment is as follows:
[0042] The water-based resin, quartz sand, tailings sand and surfactant are mixed by measuring, and then silicate cement and anti-icing agent are added to serve as the surface material of the brick.
[0043] The aggregate is metered and wetted with water and introduced into the drum along one end of the first feeding drum. The PLC controller starts the motor to drive the gear and the gear ring to rotate. At this time, the drum starts to rotate slowly, driving all the 0mm-3mm iron tailings and 3mm-5mm basalt aggregates to roll. When the above-mentioned aggregates are pushed to the top of the drum cavity by the baffle fixedly connected in the drum, they fall down due to the action of gravity.
[0044] On one side of the drum, all the mixed cement, reduced iron powder, anti-icing agent and water reducer are mixed evenly by the mixer and introduced into the auger through the mixer outlet. The start of the auger pushes the above mixture into the second feeding barrel. The mixture pushes the limit plate and enters the side of the limit plate close to the drum.
[0045] When the aggregate falls from the top of the drum, the PLC controller will control the high-pressure air source to pass high-pressure pulse air into the second air inlet pipe and the first air inlet pipe, driving a certain amount of mixture into the drum. The falling aggregate will collide with the mixed powder, and the mixture will be contaminated on the outside of the aggregate. The first air inlet pipe can offset the blowing force of the second air inlet pipe and distribute the mixture more evenly in the internal space of the drum, making it easier for the aggregate to adhere to the mixture. Repeat the above actions, and the aggregate will adhere to a certain thickness of the mixture and form a ball.
[0046] The stirred surface layer material and the spherical bottom layer material are put into the hopper of the brick making machine respectively, and the shock-compression molding machine starts to automatically make bricks.
[0047] After the permeable snow-melting bricks are made, they need to be put into the curing kiln for curing. The curing kiln temperature should be controlled below 40 degrees and the humidity should be controlled at about 85%. The curing time is 36 hours.
[0048] After leaving the kiln, concrete hardener should be sprayed to play the role of penetration and crystallization, which not only improves the strength of the bricks but also has a slow-release effect on anti-icing materials.
[0049] In another embodiment invented:
[0050] The surface layer material and the bottom layer material of the present invention are processed respectively according to the proportions in the following table.
[0051]
[0052]
[0053] In a closed laboratory, the temperature was -10℃±1℃, the air pressure was normal atmospheric pressure, and simulation experiments were conducted based on the annual average snowfall frequency of 20 times in North China. The results showed that the service life of ordinary permeable bricks could reach 30-40 times, while the permeable bricks of the present invention could reach 40-80 times.
[0054] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for manufacturing a PC imitation stone permeable brick capable of melting snow, characterized in that: The steps include: S1. Proportion of the surface materials of the permeable bricks: The surface layer is divided into cementitious materials and auxiliary materials, wherein the cementitious materials include water-based resin and silicate cement; the auxiliary materials include quartz sand, tailings sand, anti-icing agent and surfactant, and the cementitious materials and auxiliary materials are stirred and mixed according to the proportion; S2. Ratio of bottom materials of permeable bricks: The bottom layer includes mixed cement, condensation nucleus material, reduced iron powder, anti-icing agent and high-efficiency water reducing agent. The condensation nucleus material is used as the core to mix the mixed cement, anti-icing agent and high-efficiency water reducing agent into a spherical shape; S3, shock-pressing forming: the surface layer material and the bottom layer material are successively put into the shock-pressing brick-making machine to form the primary product of the permeable brick through shock-pressing; S4. Enhanced product functions: After the permeable bricks are cured in the curing room, hardener and anti-icing coating are sprayed on their surface.
2. The method for manufacturing the snow-melting PC imitation stone permeable brick according to claim 1, characterized in that: The water-based resin in the cementitious material accounts for 3%-8%, and the silicate cement accounts for 3%-8%; the auxiliary materials include quartz sand accounting for 5%-15%, tailings sand accounting for 60%-80%, anti-icing agent accounting for 3%-10%, and surfactant accounting for 1%-5%. The above percentages are all mass percentages.
3. The method for manufacturing the snow-melting PC imitation stone permeable brick according to claim 1, characterized in that: The mixed cement in the base material accounts for 15%-25%, 0mm-3mm iron tailings and 3mm-5mm basalt account for 60%-75%, reduced iron powder accounts for 3%-8%, anti-icing agent accounts for 3%-10%, and high-efficiency water reducer accounts for 1%-5%. The above percentages are all mass percentages; the mixed cement is a mixture of silicate cement and aluminum sulfate cement in a 1:1 ratio.
4. The method for manufacturing the snow-melting PC imitation stone permeable brick according to any one of claims 1 to 3, characterized in that: The anti-icing agent is one or more combinations of Mafilon, sodium chloride, calcium chloride or potassium acetate.
5. The method for manufacturing the snow-melting PC imitation stone permeable brick according to claim 1, characterized in that: The surfactant is one or more of anionic, nonionic or amphoteric surfactants, and is used to improve the dispersibility and fluidity of the material.
6. The method for manufacturing the snow-melting PC imitation stone permeable brick according to claim 1, characterized in that: The reduced iron powder is iron powder that has been subjected to reduction treatment, and its particle size is controlled below 100 meshes to ensure that it fully reacts with the infiltrated water to release heat.
7. The method for manufacturing the snow-melting PC imitation stone permeable brick according to claim 1, characterized in that: The high-efficiency water reducing agent is one or more of polycarboxylic acid-based, naphthalene-based or lignin-based high-efficiency water reducing agents, and is used to reduce water consumption and improve the density and strength of permeable bricks.